Peripapillary perfused capillary density in exfoliation syndrome and exfoliation glaucoma versus POAG and healthy controls: An OCTA study - Yanin Suwan (2018)
Copyright © 2017 Asia-Pacific Academy of Ophthalmology. Unauthorized reproduction of this article is prohibited. Purpose: To compare the peripapillary perfused capillary density (PCD) among eyes with exfoliation syndrome (XFS), exfoliation glaucoma (XFG), primary open-angle glaucoma (POAG), and controls. Design: Observational, cross-sectional study. Methods: Optical coherence tomography angiography (OCTA) images (4.5 × 4.5 mm) of the optic nerve head were obtained using a commercial spectral domain OCTA system (AngioVue Avanti RTVue-XR, OptoVue, Fremont, CA). Two concentric circles with 1.95-mm (inner) and 3.45-mm (outer) diameters were placed manually, producing an annulus of width 0.75 mm centered at the optic disc. PCD was calculated as the ratio of pixels associated with capillaries to the pixels in the annulus after large blood vessel removal. Continuous variables were assessed by analysis of variance and Tukey honest significant difference (HSD) test. Multiple linear regression analysis was performed to adjust for confounding factors. Results: Forty-three XFG eyes, 31 POAG eyes matched for visual field mean deviation, 33 XFS eyes, and 45 control eyes were analyzed. PCD demonstrated a progressive decrease from controls to XFS to POAG to XFG. Pairwise comparisons revealed significant differences in PCD between each pair of groups (all P < 0.01) except for PCD between XFS and POAG (P = 0.08). A multivariable model adjusting for age and stage showed a more significant decrease in PCD in XFG compared with POAG (P = 0.001). Conclusions: PCD was more significantly decreased in XFG compared with POAG eyes and in XFS compared with control eyes. OCTA provides the first quantitative evidence of the microvascular disturbance that accompanies XFS.